Modern Brainstem MRI Techniques for the Diagnosis of Parkinson's Disease and Parkinsonisms - Arribarat, Germain; De Barros, Amaury; Péran, Patrice (Frontiers in Neurology, 2020)
The brainstem is the earliest vulnerable structure in many neurodegenerative diseases like in α-Synuclein-related pathologies such as in Multiple System Atrophy (MSA) or Parkinson’s disease (PD). Up-to-now, MRI studies have mainly focused on whole-brain data acquisition. Due to its spatial localization, size and tissue characteristics, brainstem poses particular challenges for MRI. We provide a brief overview on recent advances in brainstem-related MRI markers. Several MRI techniques investigating brainstem, mainly the midbrain, showed to be able to discriminate PD patients from controls or to discriminate PD patients from atypical parkinsonism patients: iron-sensitive MRI, nigrosome imaging, neuromelanin-sensitive MRI, diffusion tensor imaging and advanced diffusion imaging. A standardized multimodal brainstem-dedicated MRI approach at high resolution able to quantify microstructural modification in brainstem nuclei would be a promising tool to detect early changes in parkinsonian syndromes.